Gambaran Profil Darah Ayam Lokal dengan Suplementasi Probiotik Lactobacillus sp. dan Bacillus subtilis pada Pakan: Blood Profile of Local Roosters with Probiotic Supplementation of Lactobacillus sp. and Bacillus subtilis in Feed - Alditya Putri Yulinarsari; Ningsih, Niati; Muhamad, Nur; Syaikullah, Gayuh; Dewi, Aryanti Candra (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2025)
Local Rooster is potentially to be developed, because it has adaptive characteristics and is easy to raise. Giving probiotics to local rooster is considered important to increase endurance and decrease mortality in livestock. The purpose of the study was to determine the effect of single-strain or multistrain probiotic supplementation, namely Lactobacillus sp. and Bacillus subtilis. This study used a Completely Randomized Design (CRD) with four treatments and five replications, namely P0: Feed + 0% Probiotic; P1: Feed + 1% Single Probiotic Bacillus subtilis; P2: Feed + 1% Single Probiotic Lactobacillus sp.; P3: Feed + 1% Multi Probiotic Bacillus subtilis and Lactobacillus sp. The blood profiles observed were hemoglobin, erythrocytes, hematocrit, erythrocyte indices consisting of Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH), and Mean Corpuscular Hemoglobin Concentration (MCHC), leukocytes, neutrophils, lymphocytes, monocytes, and platelets. Data was analyzed using Analysis of Variance (ANOVA) and continued using Duncan Multiple Range Test (DMRT). The study results showed a significant effect between treatments (p<0.05) in the MHC content in the blood of local roosters. However, all treatments had no effect on other blood parameters. It can be concluded that supplementation of a single probiotic of B. Subtilis and Lactobacillus sp. could reduce the MCH value of the Local Rooster then improve the body's immune system. However, it did not affect the number of hemoglobin, erythrocytes, hematocrit, MCH, MCHC, leukocytes, lymphocytes, monocytes, and thrombocytes. Key words: Bacillus subtilis, blood profile, Lactobacillus sp., local roosters, probiotic